Direct preparation of battery‐grade lithium carbonate via a nucleation–crystallization isolating process intensified by a micro‐liquid film reactor. (25th May 2022) - Tan, Jianghao; Wang, Qi; Lin, Yanjun; Xiang, Xu
Abstract: With the lithium‐ion battery industry booming, the demand for battery‐grade lithium carbonate is sharply increasing. However, it is difficult to simultaneously meet the requirements for the particle size and the purity of battery‐grade lithium carbonate. Herein, the nucleation–crystallization isolating process (NCIP) is applied to prepare battery‐grade lithium carbonate without any post‐treatment procedure. The nucleation process is intensified by a micro‐liquid film reactor (MLFR), where the feedstock solution is subject to intensive shear force and centrifugal force. The feedstock solutions are mixed rapidly and a large number of nuclei form instantly in the MLFR. After nucleation, the crystallization process is achieved in another reactor. A few new nuclei form in the crystallization process. The nucleation intensification in the MLFR is verified by computational fluid dynamics (CFD) simulations and experimental results. The particle size distribution is narrower and the impurity residue in the products is far lower than that prepared by a traditional precipitation method. The effects of nucleation and crystallization on the particle size distribution and purity were investigated. In the optimized operation parameters, the particle size distribution of the Li2 CO3 product is D 10  = 2.856 μm, D 50  = 5.976 μm, and D 90  = 11.197 μm, and the purity is 99.73%, both of which meet the requirements of battery‐grade Li2 CO3 . Moreover, the lithium recovery rate is increased to 88.21% compared to that prepared by a traditional precipitation method (79.0%). This work provides an alternative way for the preparation of high‐purity chemicals by process intensification. Abstract : A nucleation–crystallization isolating process is applied to prepare battery‐grade lithium carbonate, in which the nucleation process is intensified by a micro‐liquid film reactor.